Abu Al-Hasan Al-Rum in the book (Al tanbeah wa Al Alshraf) by Al-Masoudi, a study of their geographical and religious situations - محمد حسب الله علوان, م . د (lark, 2021)
The historian and geographer and globetrotter Abo AL Hassan Ali bin AL Hussain AL masoudi is one of the most important  historian in the ( Fourth century A G/ TEN AD) and one of the most important pioneers at litreture of geographer, as he contributed through his scientific production to provide the historical and geographic library by the value information, escpcially in the history and civilizion of the state and other kingdoms  which were longdistance and near to the I slamic Arab nation, and his authoresses vegarded an important source to the mang of historains and researcher, at studying  the religions, society and geographg for a lot of the nation and know what had from history and civilization multifariousness of the information is one of the characterized that the writing, of( ALtanbeah wa AL AL shraf) the focus of our reseach, which was regarded scientific encgclopedia that we cant dispensed fromit in the study of the history ingeneral and the country of Rome in particular and the historian ( AL masoudis) presented for us an important geographical perceptions by previewing the extended geographic larea. In this country that has mountains, lake, bays, and roads, and he mentioned the geographical advantages for mange important cities in the country of Rome such as (Constantinpole) and (Roma) and other. AL masoudi presented for in this book perception of the religious situation in the Rome country especially at the beginning of emergence and spread of christianty and the things which associated with differences in beliefs. And also the holding of church conferences .that result fromit appearing different religious groups as well as places of worship religious. Title and ranks in Roman countries. The research includes an introduction three topics and conclusion. In the first topic we talked about Al-mosoudi and his book (Al tanbeah wa Al shraf) .the second topic was devoted the geographical condition in the countries of the Romans in the book (Al tanbeah wa Al shraf). And at the third topic we talked about the religious condition in Rome country in his book (Al tanbeah wa Al shraf)
Keywords: rum. Al-Masoudi. Alert and supervision. Geography. Debt